Parliamentary integrity systems in Europe – the personal-responsibility dimension. Issue 4 (1st October 2020) - Blomeyer, Roland
ABSTRACT: The failure of members of parliament to act with integrity undermines trust in democracy (Allen, N. 2010. Keeping MPs honest? Public Integrity, 12 (2), 105–123). To enhance trust, parliaments have introduced 'Parliamentary Integrity Systems'. Research on integrity systems shows that to be effective a system needs to address two key dimensions of integrity, namely the legal-institutional and the personal-responsibility dimension (Dobel, P. 1999. Public integrity . The John Hopkins University Press). Whilst the first dimension relates to rules and their enforcement, the second is concerned with prevention, or strengthening the understanding and capacity of actors to embrace integrity. To what extent do the existing systems address the two dimensions of integrity? To answer this question, this article reviews 46 Parliamentary Integrity Systems, drawing on data collected by the 'Group of States against Corruption' of the Council of Europe. This article finds that Parliamentary Integrity Systems have failed to speak in a balanced way to the two dimensions, with the focus clearly on rules and their enforcement and limited attention to prevention. The article concludes by noting relevant areas for future research, aiming to enhance insights into the effectiveness of the personal-responsibility dimension of integrity.